Ungkapan 100% Katolik 100% Indonesia dan Kaitannya dengan Peribadatan Umat di Tangerang - Brigita, Agnes; Fauzi, Agus M. (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2022)
The Catholic Church during this pandemic also urges its followers to comply with all government policies and changes in the social conditions of the people which have changed a lot and have caused many changes in people's attitudes as well as to continue their lives, leading to the birth of the phrase